2020
DOI: 10.1109/jeds.2020.2974576
|View full text |Cite
|
Sign up to set email alerts
|

Pixel Circuit With Leakage Prevention Scheme for Low-Frame-Rate AMOLED Displays

Abstract: This work proposes a new pixel circuit for active-matrix organic light-emitting (AMOLED) smartwatch displays with a low frame rate. Within the long emission period, the leakage current of a lowtemperature polycrystalline silicon thin-film transistor (LTPS TFT) is reduced to suppress the distortion of the driving voltage at the gate node of the driving TFT. Based on the measured electrical characteristics of a fabricated p-type LTPS TFT, the HSPICE model is established to verify the feasibility of the proposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 16 publications
2
12
0
Order By: Relevance
“…Based on the proposed pixel structure with two in-pixel signal lines, the subpixel layout area is estimated to be 42 µm × 21 µm, and is suitable for portable displays. Moreover, it shows that the error rate of 2.71% in the study is better than that of the reference [13] and is comparable to the references [15,16]. It was also found that the error rate is increased with the increasing ∆V TH_DTFT , because more compensation time would be needed for our pixel to achieve the varied V TH_DTFT .…”
Section: Resultssupporting
confidence: 63%
See 3 more Smart Citations
“…Based on the proposed pixel structure with two in-pixel signal lines, the subpixel layout area is estimated to be 42 µm × 21 µm, and is suitable for portable displays. Moreover, it shows that the error rate of 2.71% in the study is better than that of the reference [13] and is comparable to the references [15,16]. It was also found that the error rate is increased with the increasing ∆V TH_DTFT , because more compensation time would be needed for our pixel to achieve the varied V TH_DTFT .…”
Section: Resultssupporting
confidence: 63%
“…It was also found that the error rate is increased with the increasing ∆V TH_DTFT , because more compensation time would be needed for our pixel to achieve the varied V TH_DTFT . Although these reported circuits [13][14][15][16] could compensate for the ∆V TH_DTFT , only the presented pixel circuit has the ability to simultaneously achieve low-voltage driving and low frame rate, with only two signal lines including SN and EM in a pixel. Thus, the presented pixel circuit using an LTPO TFT is suitable to compensate for the ∆V TH_DTFT for high-pixel-density portable AMOLED displays.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…is always one of the most important requirements. Low frame rate operation has been considered as one very effective scheme to reduce the power consumption of display panels [9]. However, it is very difficult to have the LTPS TFT-based AMOLED displays operating at a low frame rate, as the LTPS TFT usually has a high off-current, which restricts the low limit of the frame rate [7], [10]- [12].…”
Section: Introductionmentioning
confidence: 99%